Production of Adult Human Synovial Fluid-Derived Mesenchymal Stem Cells in Stirred-Suspension Culture - Kristen D. Jorgenson; David A. Hart; Roman Krawetz; Arindom Sen (Stem Cells International)
The chondrogenic potential of synovial fluid-derived mesenchymal stem cells (SF-MSCs) supports their use in cartilage regeneration strategies. However, their paucity in synovial fluid necessitates their proliferation in culture to generate clinically relevant quantities. Here it was determined that 125 mL stirred suspension bioreactors utilizing Cytodex-3 microcarrier beads represent a viable platform for the proliferation of these cells. During the inoculation phase, a bead loading of 2 g/L, an inoculation ratio of 4.5 cells/bead, and continuous agitation at 40 rpm in a medium with 5% serum resulted in high cell attachment efficiencies and a subsequent overall cell fold expansion of 5.7 over 8 days. During the subsequent growth phase, periodic addition of new microcarriers and fresh medium increased culture longevity, resulting in a 21.3 cell fold increase over 18 days in the same vessel without compromising the defining characteristics of the cells. Compared to static tissue culture flasks, a bioreactor-based bioprocess requires fewer handling steps, is more readily scalable, and for the same cell production level, has a lower operating cost as it uses approximately half the medium. Therefore, stirred suspension bioreactors incorporating microcarrier technology represent a viable and more efficient platform than tissue culture flasks for the generation of SF-MSCs in culture.